2021
DOI: 10.21037/tp-20-192
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography evaluation of bronchopulmonary dysplasia-associated pulmonary hypertension: a retrospective observational cohort study

Abstract: Background: Echocardiography has poor accuracy in grading the severity of pulmonary hypertension (PH) compared to cardiac catheterization. However, the relationship between degree of PH and prognostic outcomes remains uncertain. Our primary objective was to determine whether echocardiogram-assessed PH severity is associated with mortality and hospital readmission in the first year of life.Methods: A retrospective cohort study of infants born less than 32 weeks of gestational age with bronchopulmonary dysplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Du et al reported that the number of patients with mild PH was threefold higher than the number of patients with moderate to severe PH in their study. 12 They also noted that patients with moderate to severe PH accounted for an estimated 5.9% of all patients, similar to the present results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Du et al reported that the number of patients with mild PH was threefold higher than the number of patients with moderate to severe PH in their study. 12 They also noted that patients with moderate to severe PH accounted for an estimated 5.9% of all patients, similar to the present results.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, pulmonary hypertension (PH) associated with BPD is considered important, because more severe preterm newborns have been saved by the recent advanced intensive neonatal management 7–9 . There have been some studies about PH associated with BPD, but they were based on patient data from a single or small number of institutions 4,10–15 . To determine the actual incidence of PH associated with BPD in VLBWIs, a cohort survey is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that between 8-42% of infants with BPD have evidence of PH 1,2,3,4,6 . Mortality rates for infants with BPD-PH have been reported to be as high as 47% 3,4,6,7,8 . In addition, there is a growing appreciation that the individual and societal costs associated with BPD-PH are substantial 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Premature infants with chronic lung disease of prematurity, bronchopulmonary dysplasia (BPD), are at risk of developing pulmonary hypertension (PH) 1,2,3,4,5,6 . It has been estimated that between 8-42% of infants with BPD have evidence of PH 1,2,3,4,6 . Mortality rates for infants with BPD-PH have been reported to be as high as 47% 3,4,6,7,8 .…”
Section: Introductionmentioning
confidence: 99%